1978
DOI: 10.1002/j.2333-8504.1978.tb01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Differentially Difficult Items as an Approach to Test Bias

Abstract: SUMMARY In this study, a substantial number of items that were appreciably more difficult for Black than for White students were eliminated from a verbal test and from a mathematical test. Shortening the tests by this method had relatively little effect on score differences between Black and White students. This method of selecting items for elimination resulted in tests that were decidedly more difficult for both student groups. These outcomes clearly limit the value of this method for use in developing tests. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Flaugher & Schrader (1978) removed a substantial number of items from the SAT-V and SAT-M that were appreciably more difficult for black than for white students and found that removal of the items had little effect on total score differences between black and white groups. In fact t removing these items made the tests more difficult for both groups.…”
Section: Factor Analysis Methodsmentioning
confidence: 99%
“…Flaugher & Schrader (1978) removed a substantial number of items from the SAT-V and SAT-M that were appreciably more difficult for black than for white students and found that removal of the items had little effect on total score differences between black and white groups. In fact t removing these items made the tests more difficult for both groups.…”
Section: Factor Analysis Methodsmentioning
confidence: 99%
“…Our aim was to create tests that would adhere to operational content and statistical specifications but at the same time exhibit Black/White differences in scores as small and as large as possible under the constraints imposed by the test specifications and the size of our available item pool. To our knowledge this has never been done before, although related research may be found in: Flaugher and Schrader (1978), Green (1972), Ironson and Craig (1982), Kok et al (1985) and Subkoviak et al (1984).…”
Section: Introductionmentioning
confidence: 91%
“…and Validity There are a number of relationships between impact, item difficulty, test reliability and validity that must be considered when we interpret the results of the approaches used in this paper. The effect of these relationships has also constrained the results of previous studies such as Hackett, Holland, Pearlman, & Thayer (1987) and Flaugher & Schrader (1978) but was not explicitly recognized.…”
Section: Impactmentioning
confidence: 97%
“…Some authors assume any differences are irrelevant (e. g., Rosser, 1987;Weiss, 1987) and argue that the fairest test is assembled by choosing items that minimize group mean score differences, regardless of the effect on the construct intended to be measured by the test. A variation on this theme is the argument based on the work of some researchers (e. g., Carlton and Harris, 1992;Gallagher, 1992;Schmitt and Crone, 1991) that groups differ on average on classes of items, and that fairer tests may be produced by changing the construct being measured and eliminating just those classes of items (e. g., Flaugher and Schrader, 1978). Still other authors argue that the only irrelevant differences are those remaining after conditioning on test score, which has lead to the study of Differential Item Functioning (DIF; Holland and Thayer, 1988).…”
Section: Introductionmentioning
confidence: 99%